Translation Shift of Chinese-Indonesian Subtitle in Our Times Movie - Meutia Noor Alizah Polem (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Movie is an art which has an aesthetic purpose. It is used to be a form of entertainment, but as time goes by, movie can be used as a media to spread certain messages to the public. One of those movies is from China and the language is Chinese. Therefore, it is necessary to have a movie translation from Chinese to Indonesian, which uses subtitle translation. In a process of translation, the shifting of translation is found for most of the time. This research aims to find out two problems of the research. First, the translation shift form from the result of translation subtitle. Second, the form of shifting translation mostly found in the subtitle of movie called Our Times. The object of this research is the Our Times movie《我的少女时代》wŏ de shăonǚ shídài. The film is in Chinese with Chinese subtitles and translated into Indonesian. This research only focuses on shifting the translation results in Mandarin-Indonesian subtitles on the Our Times movie《我的少女时代》wŏ de shăonǚ shídài. The method used in this research is descriptive qualitative with the approach of instrumental study. The result of the research shows that the subtitle of Our times movie there are 86 data divided into six kinds of translation shift, which are about: Structure Shift (37,21%); Intra Shift System (19,77%); Level Shift (12,79%); Down Rank Shift (11,63%); Class Shift (9,30%); and Up Rank Shift (9,30%). Due to the difference in grammatical structure and the culture which are supported by the use of translation procedures and techniques.